Pengaturan Tentang Penerbangan Komersial Dan Tanggung Jawab Negara - Hardianti, Hardianti; Hanafi, Irma Halimah; Riry, Welly Angela (Faculty of Law, Universitas Pattimura, 2023)
Introduction: In transportation activities, the risk of an accident is an unavoidable thing so that unification of arrangements regarding this matter is an absolute thing to do.Purposes of the Research: This study aims to find out and examine how the regulation regarding the flight of commercial aircraft in the air space of a country is reviewed from international law and how the form of state responsibility when a commercial aircraft is shot down is reviewed from international law Methods of the Research: This writing uses a normative type of legal research, which is carried out by studying theories, concepts, legal principles, and laws and regulations. In this study, the author used 2 approaches, namely the statutory approach, and the case approach.Results of the Research: The results showed that the International air law Regulation related to the parties' obligation to regulate the safety of commercial flights crossing its airspace must be in accordance with the Chicago Convention of 1944. These arrangements are made so that flights that cross the airspace of other countries can be kept safe and secure. Iran's shooting down of Ukrainian plane PS752 has violated provisions in the 1944 Chicago Convention on its airspace in an armed dispute. Therefore, Iran must take responsibility for this incident. In the future, firmness and increased cooperation with various parties are needed so that safety and security in international flights and national flights can be achieved.